[PP.29.02] METFORMIN REDUCES HIGH-FAT DIET EFFECTS ON BLOOD PRESSURE, METABOLIC PARAMETERS AND VASCULAR PROSTANOIDS IN RATS. (September 2016) - PUYÓ, A.; LEE, H.J.; Eluchans, N.M. Sánchez; Cantú, S.M.; Choi, M.R.; Donoso, A.S.; Peredo, H.A.
Abstract : Objective: Metformin (Mf) is an antidiabetic drug used in type 2 diabetes and metabolic syndrome treatment. A high-fat (HF) diet produces insulin resistance in the rat which is related to cardiovascular alterations such as hypertension. Prostanoids (PR), cyclooxygenase-derived arachidonic acid metabolites, have vasoactive properties and mediate inflammation. The aim of this study was to analyze the effect of Mf on blood pressure (BP), metabolic parameters, and mesenteric vascular bed (MVB) PR production in male Sprague-Dawley rats under a HF diet. Design and method: Four groups were studied during 12 weeks (n = 4 each): Control (C), standard diet (SD) and tap water to drink; HF diet (HF), 50% (w/w) bovine fat added to SD and tap water; C + metformin (CMf), SD + 500 mg/Kg/day Mf in the drinking water; and HF + Mf (HFMf) 50% (w/w) bovine fat added to SD + 500 mg/Kg/day Mf. PR were determined by HPLC. Results: HF diet increased body weight (BW: g, HF, 478 ± 10 vs. C, 421 ± 15 p = 0.01) % MVB/BW ratio (HF, 1.72 ± 0.8 vs. C, 0.8 ± 0.1, p < 0.001); glycemia (mg/dl, HF, 144 ± 4 vs. C, 127 ± 4, p = 0.01); triglyceridemia (mg/dl, HF, 166 ± 21 vs. C, 86 ± 9, p < 0, 01) and systolic BP (mmHg, HF, 151 ± 2 vs. C, 127 ± 2, p < 0, 001). In the HFMf group, Mf decreased MVB/BW ratio (1.38 ± 0.6, p < 0.05); glycemia, triglyceridemia, (mg/dl, 110 ± 11 vs. HF, p = 0.01; 65 ± 13 vs. HF, p = 0.01) and systolic BP (mmHg, 141 ± 1 vs. HF, p < 0.01). Moreover, HF diet increased the release of PR thromboxane (TX) B2, stable metabolite of the vasoconstrictor TXA2, (ng PR/mg tissue, HF, 121 ± 8 vs. C, 71 ± 6, p < 0, 05); and prostaglandin (PG) F2alpha (ng/mg, HF, 166 ± 11 vs. C, 87 ± 9, p < 0, 05). Mf decreased the release of (PG) F2alpha in the HFMf group (ng/mg, 81 ± 12 vs. HF, p < 0, 01). Conclusions: In conclusion, metformin treatment reduces abdominal fat which plays a role in the pathogenesis of hypertension. A possible mechanism by which metformin lowers systolic BP in this experimental model could be the reduction of vasoconstrictor prostanoid release in the MVB, reducing peripheral resistance.